The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-77602011000300018
|View full text |Cite
|
Sign up to set email alerts
|

Dominant height projection model with the addition of environmental variables

Abstract: This study investigated the behavior of climatic variables inserted as inclination modifi ers of the Chapman-Richards model for estimating dominant height. Thus, 1507 data pairs from a Continuous Forestry Inventory of clonal eucalyptus stands were used. The stands are located in the States of Espírito Santo and southern Bahia. The climatic variables were inserted in the dominant height model because the model is a key variable in the whole prognosis system. The models were adjusted using 1360 data pairs, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Although the height growth of Populus tremuloides was not significantly related to any temporal variables, Picea mariana increased with later stand establishment date, higher average maximum summer temperature between May and August, and higher atmospheric CO 2 concentrations [ 11 ]. Ferraz Filho [ 12 ] reported that the addition of climatic variables (precipitation and solar radiation) to the inclination parameters of the Chapman-Richards model resulted in more precise estimates of dominant height. Leites et al [ 13 ] concluded that the three-year height growth of Pseudototsuga menziesii was most sensitive to the mean temperature in the coldest month.…”
Section: Introductionmentioning
confidence: 99%
“…Although the height growth of Populus tremuloides was not significantly related to any temporal variables, Picea mariana increased with later stand establishment date, higher average maximum summer temperature between May and August, and higher atmospheric CO 2 concentrations [ 11 ]. Ferraz Filho [ 12 ] reported that the addition of climatic variables (precipitation and solar radiation) to the inclination parameters of the Chapman-Richards model resulted in more precise estimates of dominant height. Leites et al [ 13 ] concluded that the three-year height growth of Pseudototsuga menziesii was most sensitive to the mean temperature in the coldest month.…”
Section: Introductionmentioning
confidence: 99%